THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER’S RELATIONSHIP TOWARD PT.BANK NEGARA INDONESIA BANDUNG BRANCH’S IMAGE - Nandan Limakrisna (Jurnal Ilmiah Ekonomi Bisnis, 2009)
Competition within banking industries has been tighter lately. Banks, including BNI Bank, are required to improve their services which are more customer satisfaction oriented. Market share of Bandung branch of BNI Bank steadily decreases in the last several years. This indicates that its image is relatively low due to its service quality which is of considerably unsatisfied. The study is aimed at analyzing factors (i.e., service quality and customer relations) influencing firm image (i.e., BNI Bank Bandung Branch). Primary data were collected from respondents, who were randomly selected from customers of the bank, using a valid and reliable questionnaire. The data were analyzed using multiple linear regression analysis. Results of the study indicated that image of the bank was significantly affected by both service quality and customer relations, either partially or simultaneously. It was found that customer relations are much more important than that of service quality in influencing firm image.Key words: service quality; customer relations; firm image